Fatigue damage prediction of metro bogie frame based on measured loads. (January 2022) - Wang, B.J.; Xie, S.Q.; Li, Q.; Ren, Z.S.
Highlights: The completeness of the measured loads was verified. Bogie loads were classified into quasi-static and dynamic regions. Bogie modal vibration and rail corrugation were studied to adjust the bogie loads. The new loads were applied to predict another frame running on a different line. Abstract: The loads for bogie frame fatigue damage prediction under service environment has become a critical priority. In this study, the completeness of the measured loads was verified and bogie loads were classified into quasi-static and dynamic regions. Bogie modal vibration and rail corrugation were studied to adjust the loads. The predicted fatigue damage was closer to the actual damage and covered the measured damage. The results of this study showed that the service loads of existing frames and their characteristics can be used to predict the damage suffered by similar type of frames under similar application conditions.